2018
DOI: 10.1029/2018wr023120
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Drought Instantaneous Propagation Speed Based on the Variable Motion Relationship of Speed‐Time Process

Abstract: It is difficult to predict and track the propagation of a hydrological drought because it is hard to determine its propagation speed. We propose a useful framework for calculating the hydrological drought instantaneous propagation speed which includes the instantaneous development speed (IDS) and instantaneous recovery speed (IRS). First, the run theory was applied to subdivide the propagation of individual hydrological drought events into the development and recovery stages and to determine the individual pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 73 publications
1
33
0
Order By: Relevance
“…The information about the internal propagation, the development, and recovery of hydrological drought at the sub‐basin scale can help water managers in developing efficient water management strategies at the sub‐basin level. We used the framework suggested by Wu et al (2018) to estimate the IDS and IRS for the hydrological droughts identified during the 1901–2012 period at the 223 locations in the Indian subcontinental river basins. We compared the optimal IDS estimated using the observed and VIC model‐simulated 1‐month SSI at eight observed stations located in eight different basins (Table S2), to evaluate its applicability to 223 sub‐basins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The information about the internal propagation, the development, and recovery of hydrological drought at the sub‐basin scale can help water managers in developing efficient water management strategies at the sub‐basin level. We used the framework suggested by Wu et al (2018) to estimate the IDS and IRS for the hydrological droughts identified during the 1901–2012 period at the 223 locations in the Indian subcontinental river basins. We compared the optimal IDS estimated using the observed and VIC model‐simulated 1‐month SSI at eight observed stations located in eight different basins (Table S2), to evaluate its applicability to 223 sub‐basins.…”
Section: Resultsmentioning
confidence: 99%
“…The cross‐validation method was used to test the performance of a predictive model with an independent data set, which is not used in model development (Hu & Bentler, 1999). For the detailed description of the cross‐validation method, please refer to Wu et al (2018). Once the optimal values of IDS (IRS) using the cross‐validation method were estimated, we back predicted drought development/recovery durations (DDD pre /DRD pre ) based on optimal IDS (IRS) and TVDP (TVRP) using Equation () for all the drought events (Figure S3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These categories are meteorological, hydrological, agricultural or socioeconomic droughts. A meteorological drought describes a time period with a below average rainfall; hydrological droughts occur when there is a deficit in rainfall which affects the sub-surface moisture, surface water reservoirs and ground water; while agriculture droughts are classified when the soil moisture is low and has a negative impact on crops; and a socioeconomic drought occurs when a commodity is affected by drought conditions and there is insufficient product to meet the demand [52,53].…”
Section: Assessment Of Dry and Wet Events Using Standardized Precipitmentioning
confidence: 99%
“…Different drought definitions are proposed in literature, and droughts are generally classified in four types: meteorological, hydrological, agricultural and socio-economic [2]. Hydrological droughts (entailing a significant reduction of available surface and subsurface water variables, such as river streamflow, groundwater, reservoir and lake levels), are considered as having the most serious impacts on water supply [3,4]. In particular, the streamflows are considered as important indicators that define the status of surface water resources [5].…”
Section: Introductionmentioning
confidence: 99%